2000
DOI: 10.1262/jrd.46.397
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Abnormal Corpus Luteum in Superovulated Ewes

Abstract: Abstract. In the present study, in order to investigate the incidence time of abnormal corpus luteum (CL) in superovulated ewes, CL formation was observed and plasma progesterone (P4) and estradiol-17β(E2) profiles were investigated during the non-breeding and breeding seasons in three breeds of ewes. The ewes were treated with a fluorogesterone acetate (FGA) sponge for 12 days, and a single injection of 20 mg pFSH on Day -2 and 500 IU eCG on Day -1 (FGA sponge removal: Day 0), for estrous synchronization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
1
15
0
2
Order By: Relevance
“…We observed abnormal CL and a short cycle in the treatment phase during both seasons. This result is similar to that reported by Okada et al [21]. The present study has shown that the P 4 in two goats showing the short cycle decreased to basal levels (0.28 ng/ml) on day 4.…”
Section: Discussionsupporting
confidence: 93%
“…We observed abnormal CL and a short cycle in the treatment phase during both seasons. This result is similar to that reported by Okada et al [21]. The present study has shown that the P 4 in two goats showing the short cycle decreased to basal levels (0.28 ng/ml) on day 4.…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that the use of higher doses of FSH may lead to the persistence of luteinized anovulatory follicles, which continue to produce oestrogen during the early luteal phase and promote the early release of PGF2α and luteal regression (Okada et al, ). However, in the present study no greater number of anovulatory follicles were observed in the G200 in relation to the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the use of higher doses of FSH may lead to the persistence of luteinized anovulatory follicles, which continue to produce oestrogen during the early luteal phase and promote the early release of PGF2α and luteal regression (Okada et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations